2016
DOI: 10.1007/s10508-016-0808-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation Self-Presentation Among Bisexual-Identified Women and Men: Patterns and Predictors

Abstract: Writing on the experiences of bisexual-identified people has highlighted the potential complexity of the ongoing process of deciding when and how to present one's sexual orientation identity to others (Rust, 2002). The two studies presented here were designed to contribute basic knowledge regarding self-presentation of sexual orientation among bisexual people. In Study 1, bisexual participants (N = 147) were less likely than their lesbian and gay (LG) peers (N = 191) to present their actual orientation to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…It has been theorized that bisexuals overall face additional types of stigma and discrimination based on their sexual identity on top of the minority stress experienced by gay and lesbian individuals. In particular, they may face skepticism regarding the very existence of bisexuality, arising from the commonly held binary model of sexual orientation (e.g., homosexuality or heterosexuality), leading to perceptions that bisexuals are confused about whether they are heterosexual or gay/lesbian or temporarily experimenting (Mohr et al, 2017). Additionally, bisexual individuals in a same-gender relationship are frequently perceived as gay or lesbian, while those in an opposite-gender relationship are perceived as heterosexual, an “invisibility” that may be internalized and contribute to mental distress and social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theorized that bisexuals overall face additional types of stigma and discrimination based on their sexual identity on top of the minority stress experienced by gay and lesbian individuals. In particular, they may face skepticism regarding the very existence of bisexuality, arising from the commonly held binary model of sexual orientation (e.g., homosexuality or heterosexuality), leading to perceptions that bisexuals are confused about whether they are heterosexual or gay/lesbian or temporarily experimenting (Mohr et al, 2017). Additionally, bisexual individuals in a same-gender relationship are frequently perceived as gay or lesbian, while those in an opposite-gender relationship are perceived as heterosexual, an “invisibility” that may be internalized and contribute to mental distress and social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The process of managing one’s sexual identity and making decisions about disclosure can be especially complicated for bisexual individuals (43, 44). Bisexual and other non-monosexual individuals are more likely than monosexual individuals to identify with multiple sexual identity labels (43).…”
Section: Bisexual Minority Stressmentioning
confidence: 99%
“…In addition to using multiple identity labels, there is evidence that some bisexual individuals present their sexual orientation differently in different contexts. A recent study found that individuals who privately identified as bisexual varied in whether they publicly identified as bisexual, heterosexual, or another sexual minority identity depending on the context (44). They found that it was more common for bisexual individuals to be open about being non-heterosexual in general compared to being explicitly open about being bisexual.…”
Section: Bisexual Minority Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisexual women may not disclose their sexual orientation because of fears of encountering biphobia (Eady, Dobinson, & Ross, 2011; Ross et al, 2012) and discrimination (Koh et al, 2014; Sherman et al, 2014). They may also choose not to disclose as a result of lower salience and centrality of their sexual identity (Dyar et al, 2015), which may be especially relevant if they are have a different gender partner (Mohr, Jackson, & Sheets, 2016; Schrimshaw et al, 2013). Bisexual identities are typically invisible, since sexual identity is often presumed according to one’s partner’s gender, whereby male-partnered women are assumed to be heterosexual and female-partnered women are assumed to be lesbian.…”
Section: Sexual Identity Disclosure Among Sexual Minority Womenmentioning
confidence: 99%